Pre-operative parental anxiety in paediatric surgeries: an Asian experience - T Kumaravadivel Dharmalingam; Husnizah Zainol Abidin; Voo, Peter Su Kiong; Rajesh Kumar Muniandy (Penerbit UM, 2022)
Paediatric surgery is a traumatic experience, often accompanied by anxiety in parents. There have been many studies regarding pre-operative anxiety among children, however, there are limited studies exploring the anxiety levels of parents accompanying their child for surgery. This study aims to identify the presence of depression, anxiety, and stress among parents of children undergoing elective surgery in a tertiary hospital in Malaysia. The study population consisted of children who were scheduled for elective minor surgery between January 2018 to June 2018. The 21-item depression anxiety stress scale (DASS-21) questionnaire was used. The majority of accompanying parents had a normal depression, anxiety, and stress scores. However, there was severe to extremely severe depression, anxiety, and stress in some parents. The results showed that accompanying parents with higher level of fear tend to develop more anxiety and stress. There were no significant changes in their scores in relation to gender, history of previous surgery or history of anaesthesia clinic visit. Anxiety among accompanying parents in children undergoing surgery is an underestimated problem. It needs to be identified and managed effectively to provide better care to the child undergoing surgery and anaesthesia.